Giant polyploid epidermal cells and male pheromone production in the tephritid fruit fly Eurosta solidaginis (Diptera: Tephritidae). (April 2021) - Yip, Eric C.; Mikó, István; Ulmer, Jonah M.; Cherim, Nancy A.; Townley, Mark A.; Poltak, Steffen; Helms, Anjel M.; De Moraes, Consuelo M.; Mescher, Mark C.; Tooker, John F.
Graphical abstract: Highlights: Pheromone components detected in male pleural epidermal cells and rectum. Pleural epidermal cells are 100 times larger in males (300–400 μm) than females. In males, pleural epidermal calls are multinucleated, suggesting polyploidization. Males have cuticular elements that may help release pheromone through cuticle. Abstract: Eurosta solidaginis males produce large amounts of putative sex pheromone compared to other insect species; however, neither the site of pheromone production nor the release mechanism has been characterized. We compared E. solidaginis males and females, focusing on sexually dimorphic structures that are known to be involved in pheromone production in other tephritid species. Morphological and chemical analyses indicated that the rectum and pleural epidermis are involved in male E. solidaginis pheromone production, storage, or emission. We detected large quantities of pheromone in the enlarged rectum, suggesting that it stores pheromone for subsequent release through the anus. However, pheromone might also discharge through the pleural cuticle with the involvement of unusual pleural attachments of the tergosternal muscles, which, when contracted in males, realign specialized cuticular surface elements and expose less-sclerotized areas of cuticle. In males, pheromone components were also detected in epidermal cells of the pleuron. These cells were 60–100 times larger in mature males than in females and, to our knowledge, are the largest animal epithelial cells ever recorded. Furthermore, because these large cells in males are multinucleated, we presume that they develop through somatic polyploidization by endomitosis. Consequently, the pheromone-associated multinuclear pleural epidermal cells of Eurosta solidaginis may provide an interesting new system for understanding polyploidization.